The Proposal For Uninhabitable Housing As An Alternative For The Quality Of Life Of The Ngepanrejo Village Community - Juan Anthonio Kambuno; Tutik Wijayanti; Nur Hakim (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2022)
Housing embodies many concepts such as comfort, security, identity and most importantly, housing is of central importance to the quality of life and health of everyone, with considerable economic, social, cultural and personal significance. However, housing in Ngepanrejo Village is different, where the main housing problem at the moment is the lack of affordable accommodation for the majority of the village community, who have low incomes. Therefore, most of the housing conditions fall into the criteria for uninhabitable houses. The community in Ngepanrejo Village is struggling to uphold good quality housing in various ways, one of which is by submitting a proposal for Uninhabitable Housing. qualitative research using data collection methods in the form of secondary data. The results of this study indicate that the proposal for uninhabitable houses do make a great impact to the standard of living of the Ngepanrejo community. Through each proposals submitted every year, there are about 10 houses renovated. If this trend continues, the objective proposed by the provincial government will be achieved at a fast rate. However, most proposals are found to be mismatch to the SIMPERUM and SIKDES which is caused by human errors. This have led the village government to create a lot letter of statements just to validate that the information is correct.